V2G And G2V System Design As An Alternative Power On Microgrid With Smart Switching Method Based On Microcontroller - Alvian Aji Pangestu; Muhammad Nizam; Agus Ramelan (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
Solar energy is very easy to get in Indonesia because it is located in the tropics and equatorial regions. With the abundance of solar energy, the PLTS system is very suitable for use in Indonesia. Apart from these advantages, the microgrid system with a PV mini-grid still has drawbacks, namely intermittent sun exposure, so the reliability of the PV mini-grid system is affected by time, climate, and weather. Therefore, the PLTS system requires electrical energy storage technology in the form of batteries. In addition to the use of batteries, the use of battery electric vehicles (BEV) can also be used as an alternative to help supply power to the microgrid system. Its application uses the Vehicle to Grid (V2G) and Grid to Vehicle (G2V) methods. In this study, the design of the V2G and G2V systems was made with the Smart Switching method as an alternative power source to the microgrid system. The Smart Switching method is used to consider the condition of the battery to prevent overheating, overcharging, and deep discharging. It is equipped with a battery condition monitoring system that can be monitored on the LCD screen. The results of this study showed that the design of the V2G and G2V switching systems can run according to the plan. The system can provide power to the microgrid busbar. The system can automatically cut off when the maximum temperature, the upper and lower limits of the battery voltage, and the monitoring system can provide information in the form of battery conditions, temperature values, voltages, and currents. Thus, the V2G and G2V systems with the Smart Switching method can already be applied as an alternative power source to the microgrid system.